A comprehensive analysis of gestational trophoblastic neoplasia trials posted at online clinical trial registries. (November 2018) - Li, Jun; Li, Shufen; Yu, Hailin; Wang, Xingran; Lu, Xin
Abstract: Objective: We conducted a comprehensive analysis of gestational trophoblastic neoplasia (GTN) trials posted at online registries and aimed to provide useful information for future GTN trial designs. Study design: We searched ClinicalTrials.gov, EU Clinical Trials Register, WHO International Clinical Trials Registry Portal (ICTRP) Search Portal, Australian New Zealand Clinical Trial Registry, ISRCTN Register, and Chinese Clinical Trial Register for all the clinical trials reporting GTN treatments. The general information of each trial was extracted. Results: Twenty trials meeting the inclusion criteria were included in the final analysis. In total, 6 trials were phase II trials, 2 were phase II/III trials, 7 were phase III trials, and 1 was a phase IV trial; and the phase type of 4 trials were not reported. The conditions included low-risk GTN (n = 15), high-risk GTN (n = 2), and mixed GTN (n = 3). Randomization was performed in 15 trials, and the remaining 5 trials were single-arm trials. The median enrollment size for randomized clinical trials (RCTs) and single-arm trials was 80 and 38, respectively. Among the RCTs, parallel assignment was used in 12 trials, crossover assignment was used in 1, and the intervention models of 2 were not reported. For masking, 15 trials were open-label, 2 were single-blinded, 2 were double-blinded, and the masking status of 1 was not reported. Ovarian functions and pregnancy outcome after chemotherapy were evaluated in only 2 trials. Regarding sponsorship, 2 trials had industry sponsorship. Conclusion: Conducting RCTs for GTN is challenging, and international collaboration and smarter clinical trial designs are required for future GTN trials.